2019
DOI: 10.1136/neurintsurg-2018-014540
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular mechanical thrombectomy for acute stroke in young children

Abstract: BackgroundMechanical thrombectomy has emerged as a standard of care for acute stroke from large vessel occlusion in adults but remains controversial in children. Cerebral vessels are nearly adult size by 5 years of age but the technical feasibility of achieving recanalization in younger and smaller children with current endovascular tools remains unclear.ObjectiveTo systematically review the literature on mechanical thrombectomy for stroke in children less than 5 years of age.ResultsMechanical thrombectomy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…There are several case reports and series of cases on mechanical thrombectomy in children, documenting the efficacy of this technique, as well as its safety, in a similar fashion as in adult patients. 4 , 8 , 10 , 13 , 1621 Presently, several literature reviews and systematic reviews have already been published on thrombectomy in large vessel occlusion pediatric stroke. 2 , 8 , 9 , 11 , 12 , 2225 Table 2 summarizes the largest recent series of cases in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several case reports and series of cases on mechanical thrombectomy in children, documenting the efficacy of this technique, as well as its safety, in a similar fashion as in adult patients. 4 , 8 , 10 , 13 , 1621 Presently, several literature reviews and systematic reviews have already been published on thrombectomy in large vessel occlusion pediatric stroke. 2 , 8 , 9 , 11 , 12 , 2225 Table 2 summarizes the largest recent series of cases in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Compatibility with devices used for adults seems to be an issue only until 5 years of age, from which point on intracranial vessels will have reached the adult proportions. 20 , 40 The use of smaller catheters/stent retrievers should be considered in smaller children. In the youngest patient in our series (2 year-old), a 3 mm stentriever was used, as well as a 3 F aspiration catheter.…”
Section: Discussionmentioning
confidence: 99%
“…9,11 With the advent of hyperacute therapies for the treatment of AIS and emerging evidence that these interventions may be safe and effective in children, it is imperative that children with AIS are identified in a timely fashion. [1][2][3][4][5][6] This requires enhanced community education and an organized system of evaluation and management once a patient presents for medical care. 20 We have shown that the establishment of a stroke alert system at a tertiary children's hospital, coupled with extensive internal educational efforts, significantly decreases the median time to diagnosis by neuroimaging of patients presenting to the ED with brain attack symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, children with AIS are also being treated successfully with IV-tPA and mechanical thrombectomy. [1][2][3][4][5][6] The implementation of hyperacute therapies requires the timely identification of stroke, which has historically proved challenging in children; the median time from symptom onset to diagnosis of AIS in children is more than 20 hours. [7][8][9][10][11][12] A delay in diagnosis, coupled with the apparent safety and efficacy of IV-tPA in children, prompted 23 pediatric centers in North America to develop multidisciplinary stroke teams capable of emergent, around-the-clock response to patients with acute-onset focal neurologic deficits, 13,14 otherwise known as brain attack symptoms.…”
mentioning
confidence: 99%
“…According to Felling et al, paediatric ischaemic stroke has an estimated adjusted incidence of 1.6 x 100,000 per year [1], which is lower than the incidence of stroke in adults, and the overall lifetime risk of acute ischaemic stroke is, on average, 18.3% in Western Europe [2]. In adults, posterior fossa strokes occur four times less frequently than anterior circulation strokes and are generally linked to atherosclerotic disease [3]. In children, posterior fossa strokes were linked (45%) to vertebral artery dissection (V2-V3 traits), mainly trauma-related dissection [4][5].…”
Section: Introductionmentioning
confidence: 99%